(untitled) (Veterinary Science, 2020)
Chronic kidney disease occurs frequently in dogs and has a prevalence of 0.5-1.5%. The filtration, reabsorption and renal excretion processes allow homeostasis to be maintained in living organisms. These processes are affected, in renal lesions, resulting in organ failure. The following factors constitute a risk for the development of chronic kidney disease: both acute and chronic infections, neoplasms, immunomediated diseases, arterial hypertension, endocrinopathies, administration of corticosteroids and non-steroidal anti-inflammatory drugs, metabolic alterations, increased uric acid in the blood and advanced age. . The objective of this study was to determine the association between the presence of risk factors for chronic kidney disease and those analyzes that can be taken as indicators of impaired renal function. 31 dogs aged ≥8 years and / or at some risk factor to develop chronic kidney disease were studied. The present study was carried out in the clinical offices and the Clinical Analysis laboratory of the School Hospital of the Faculty of Agronomy and Veterinary Medicine, of the National University of Rio Cuarto. Patients were selected and recorded in clinical records the following data: review, history, physical examination, clinical signs, diagnosis, prognosis, treatment. Blood and urine samples were taken for laboratory analysis. Laboratory results: the blood count showed no variation in relation to renal processes; in urinalysis, 5 dogs showed isostenuric density, without proteinuria; 8 presented proteinuria and 2 of them with urine cylinders. In relation to blood biochemistry, creatinine was observed increased in 5 patients; the rest of the blood data without relevant variations. In the urinary biochemistry, the Na Exculsion Fraction stood out whit 9 patients with increase; and Protein ratio: Creatinine: 4 patients with increase. It is concluded that from the data evaluated the most specific and early indicators of chronic kidney disease, in patients with risk factors for their development, are the Fraction of Na Exclude and Protein: Creatinine Ratio, both in urine. Its measurement is suggested in patients with risk factor to develop chronic kidney disease.